Performance of different configurations of rooftop rainwater harvesting used for managed aquifer recharge: a stormwater management approach in an urbanized area - Baptista, Victor Santos Galvão (2020)
The urbanization process in urban coastal areas has led to intense groundwater consumption whereas reducing permeable areas and increasing the frequency and magnitude of floods. To compensate these adverse effects, this research investigated the performance of different configurations of rooftop rainwater harvesting systems as tools for at-source managed aquifer recharge and sustainable stormwater management in a Brazilian coastal city located in a sedimentary aquifer system. Several combinations of rooftop area and water tank capacity were tested. The systems are connected to the unconfined Barreiras Formation through a six-inch diameter injection well. Rainfall-runoff processes and water balances were simulated from monitored, high-temporal resolution, rainfall data and insights acquired after experimental tests results (pumping tests and injection tests). Results show that these systems can provide mean annual rainwater retention rates higher than 50% for most studied configurations (tanks capacity higher than 3 m³ and catchment areas ranging from 10 to 5,000 m²). When managed aquifer recharge is the priority of a rainwater harvesting system, results indicate that rainwater retention rates of 75% or higher must be pursued. Lower rates would only produce substantial increases in runoff overflowing to the downstream drainage network. When flood control and mitigation is pursued, the efficiency of the system must be close to 100%, a fact that produces rainwater retention close to 100% as well. This study shows the importance of coordination of sustainable urban drainage solutions and managed aquifer recharge schemes, an approach that can contribute to raising the groundwater supply in urban areas while reducing the risk and severity of floods.